Work Engagement in Nurses during The Covid-19 Pandemic: A Literature Review - Miawati, Tita; Tukiran, Martinus; Anggorodi , Riza (Journal of Industrial Engineering & Management Research, 2021)
In this research we aim to determine the factors that influence the nurse’ work engagement to be a foundation of knowledge to guide best practice to COVID-19 pandemic healthcare. This review started with identification the main topic in work engagement. The database used in, was Google Scholar and Mendeley were limited to publish from 2019-2021. The review used 3 articles that fit the inclusion criteria. This review found that front-line perceived low stress and work load, but high work engagement. The difference in work engagement of nurses working on the frontlines of the COVID-19 situation depend on their social characteristics and support. In addition, organizational identity could directly affect nursing. It can also indirectly impact nurses’ work engagement through the psychological resilience.